Aversão ao contexto associado ao estresse de derrota social em camundongos : um estudo etológico - Crestani, Ariela Maltarolo (Universidade Federal de São Carlos, 2015)
Aggressive interactions between conspecific animals have been used as an ethological source of social stress to study some aspects of social anxiety. Through this work we used a new experimental protocol in order to develop a new behavioural paradigm in the study of social anxiety. Mice were exposed to an apparatus adapted from rat exposure test (RET) and it consisted of three interconnected regions: home chamber, tunnel and surface area. Animals were exposed to the experimental apparatus for five consecutive days, being the first three days for habituation to the apparatus (habituation 1 , 2 and 3) and on the fourth day occurred the social interaction between conspecifics (not aggressive for animals from "non-defeated group" and aggressive for animals from "defeated group"). On the fifth and final experimental day the animals were re-exposed to the apparatus for 10 minutes and the following behaviors were assessed: frequency of entries and time spent in the three regions of the apparatus (home chamber/tunnel/surface area), frequency of the stretched attend posture (SAP) behaviour in the three regions, time spent on self-grooming in the three regions, frequency of rearing in the surface area and latency to reach the surface area once the animals were re-exposed to the experimental apparatus. Factor analysis was used in this study to trace the behavioural profile of socially defeated mice (n=90) when re-exposed to the apparatus where the aggressive interaction occurred; we also compared the behavioural profile of non-defeated (n=89) and defeated (n=90) mice when re-exposed to the context where social (non-aggressive or aggressive) interaction occurred, using Student’s t test. Final factor analysis yielded 4 factors that together represent 72.09% of total variance: factor 1 was loaded with time spent in the home chamber and in the surface area and self-grooming in the home chamber, while factor 2 loaded on time spent in the tunnel and total entries in the three compartments of the apparatus (home chamber, tunnel and surface area). Factor 3 was loaded with SAP frequency in the tunnel and in the surface area; and factor 4 was loaded only with latency to reach the surface area. Student’s t test showed that socially defeated mice spent more time to reach the surface area and performing self-grooming in the home chamber when compared to non-defeated mice. Together, these results suggest that the increase in the latency to reach the surface area and self-grooming in the home chamber were conditioned to a single social defeat, but there were no conditioning for classical measures such as: place aversion and risk assessment behaviour (SAP).
Keywords: Ansiedade; Ansiedade social; Modelos animais; Condicionamento contextual; Análise fatorial; CIENCIAS BIOLOGICAS::FISIOLOGIA